220 GHz Multi Circuit Integrated Front End Based on Solid‐State Circuits for High Speed Communication System. Issue 3 (1st May 2022) - NIU, Zhongqian; ZHANG, Bo; DAI, Bingli; ZHANG, Jicong; SHEN, Fang; HU, Yi; FAN, Yong; ZHANG, Yihan
Abstract : This paper presents the research on a 220 GHz multi circuit inte‐grated front end based on solid‐state circuits. This integrated front end integrates a 220 GHz subharmonic mixer, a 110 GHz tripler, a 110 GHz 8 dB hybrid coupler and a 220 GHz waveguide bandpass filter (BPF) in one single block. Compared to the traditional transceivers which usually use cascade connection of the independent mixers and multipliers, the size of the proposed multi circuit integrated front‐end block is 25 mm × 20 mm × 20 mm, ten times smaller than the cascading transceiver. In order to check the tripler's output power, a modified compact 110 GHz 8 dB hybrid coupler is set between mixer and tripler. Due to the characteristics of the hybrid coupler, the deterioration of cascading transceiver's performance caused by mismatch has also been improved. In addition, to achieve single sideband (SSB) communication, a 220 GHz BPF with high selectivity is integrated in the circuit. The measured conversion loss of the fabricated multi circuit integrated front end is less than 11 dB, where the LO and RF frequency are 37 and 210−220 GHz. Based on this front‐end, a 220 GHz high speed communication system has been setup and it can achieve 10 Gbps data transmission using 16QAM modulation.